Development of a mucoadhesive drug delivery system and its interaction with gastric cells - Sahin, Ahmet Baki; Karakurt, Serdar; Sezlev Bilecen, Deniz (Beilstein Journal of Nanotechnology, 2025)
Drugs that are designed for local treatment of gastric diseases require increased gastric residence time for prolonged action and increased efficacy. In this study, we report a mucoadhesive drug delivery system that was developed to fulfill these requirements. Alginate nanoparticles were synthesized by water-in-oil emulsification followed by external gelation and then coated with the mucoadhesive polymer Eudragit RS100. The formulated nanoparticles had a mean size of 219 nm and positive charge. A peptide, as a model drug, was loaded onto the nanoparticles with an encapsulation efficiency of 58%. The release of the model drug from the delivery system was pH-independent and lasted for 7 days. The periodic acid–Schiff stain assay indicated 69% mucin interaction for the nanoparticles, which were also capable of diffusion through artificial mucus. The nanoparticles were not toxic to gastric epithelial cells and can be internalized by the cells within 4 h. The adsorption of nanoparticles onto mucus-secreting gastric cells was found to be correlated with cell number. The delivery system developed in this study is intended to be loaded with active therapeutic agents and has the potential to be used as an alternative drug delivery strategy for the treatment of gastric related diseases.
Keywords: alginate; Eudragit RS100; mucoadhesive nanoparticles; mucus; smart drug delivery